2008
DOI: 10.1353/pbm.0.0058
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism Education: The Medical Student Response

Abstract: We present the medical students' perspective on the hotly contested topic of professionalism in medical education and explore why students are often hostile to education in professionalism. We then suggest ways to improve professionalism education in the medical curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This is also the perception of students across the country regarding their own programs [19] as the AAMC Canadian Medical School Graduation Questionnaire which is conducted across Canada at completion of medical school, found that 24% of all students (and 30% at the University of Ottawa) found the curriculum excessive. Leo and Eagen have studied why students “cringe” and feel patronized when the topic of professionalism is discussed in their curriculum [20]. They emphasize that to foster credibility, programs must promote and adhere to the same principles at all levels of training and position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also the perception of students across the country regarding their own programs [19] as the AAMC Canadian Medical School Graduation Questionnaire which is conducted across Canada at completion of medical school, found that 24% of all students (and 30% at the University of Ottawa) found the curriculum excessive. Leo and Eagen have studied why students “cringe” and feel patronized when the topic of professionalism is discussed in their curriculum [20]. They emphasize that to foster credibility, programs must promote and adhere to the same principles at all levels of training and position.…”
Section: Discussionmentioning
confidence: 99%
“…It is vital that all those who serve as role models are aware of the fundamental principles and challenges in attaining and maintaining excellence in professionalism competency. As the teachers and role models within our self-regulated profession it is our duty to take ownership of the task of developing the professionalism of our students, before someone else does [20]. …”
Section: Discussionmentioning
confidence: 99%
“…One explanation is professionalism fatigue, a pushback reaction to the recent focus in the past two decades on attempting to teach and assess professionalism [49]. Students can recognize unprofessional behaviors exhibited by faculty and physicians and are therefore more critical of the attempts to be punished for their own lapses in professionalism [21].…”
Section: Reviewmentioning
confidence: 99%
“…Students are coming to view professionalism as an “external and imposed construct,” an act they can switch on or off in order to pass testing standards such as objective structured clinical examination (OSCE’s) or under the surveillance of an attending, rather than being encouraged to instill and demonstrate the morals constituting medical professionalism [22,46]. When professionalism assessments are presented as a numerical value, with positive or negative feedback provided based on a Likert-scale, an obvious tendency is to study to achieve a high score and creating the persona of professionalism [49]. Emphasis is not being placed on the importance of these core values that will have on clinical performance and patient safety once students enter clerkship years and even into their careers.…”
Section: Reviewmentioning
confidence: 99%
“…Community-Based Participatory Research may present alternative solutions (Belone et al, 2015; Israel et al, 2008; Montoya & Kent, 2011). Others may arise out of efforts to analyze how education, socialization, and outright manipulation are persuasive forces in personal and professional identity formation (Leo & Eagen, 2008). As well, cataclysmic changes have previously prompted consideration of how to find common ground; it may well be time to revisit their effects anew (Klein, 2014).…”
Section: Further Reflectionsmentioning
confidence: 99%